2010
DOI: 10.1016/j.jhydrol.2010.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Numerically predicting seepage gradient forces and erosion: Sensitivity to soil hydraulic properties

Abstract: s u m m a r yResearch has suggested that streambank seepage can be an important mechanism of bank instability; however, limited information is available on the level of soil characterization necessary to accurately predict seepage gradient forces and erosion. The objective of this research was to quantify the expected range of predicted seepage gradients for various degrees of site characterization. Uncertainty analysis on seepage gradient predictions was performed relative to variability in soil hydraulic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The change in FOS was nearly the same as the change in RWL, which meant that the FOS increased with the increase in RWL, and the FOS decreased with the decrease in RWL. These results agreed with those of previous studies [39][40][41][42], which studied the effect of RWL on FOS. When the riverbank had a soil hydraulic conductivity lower than 10 −4 cm/s, the FOS always depended on the change in RWL because of confining pressure [42].…”
Section: Effects Of Rainfall Infiltration and River Water Level Fluctsupporting
confidence: 93%
See 1 more Smart Citation
“…The change in FOS was nearly the same as the change in RWL, which meant that the FOS increased with the increase in RWL, and the FOS decreased with the decrease in RWL. These results agreed with those of previous studies [39][40][41][42], which studied the effect of RWL on FOS. When the riverbank had a soil hydraulic conductivity lower than 10 −4 cm/s, the FOS always depended on the change in RWL because of confining pressure [42].…”
Section: Effects Of Rainfall Infiltration and River Water Level Fluctsupporting
confidence: 93%
“…A riverbank is a special slope that relates closely to hydraulic dynamics, not only from rainfall infiltration from the surface concerning the space above the slope, but also significantly from the fluctuation of the river water level and groundwater table [27,[37][38][39][40][41][42][43]. Past research works assessed the effects of rainfall on riverbank stability using the indirect process of transient seepage due to water level changes and assumed that rainfall has no effect on the riverbank surface.…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater seepage can occur in the valley, because the sandy valley side is conductive compared with the underlying tills. Some studies have shown that seepage is an important factor in bank erosion, resulting in unstable banks which can initiate and promote lateral channel migration (Fox et al, 2007(Fox et al, , 2010Van Balen et al, 2008;Eekhout et al, 2013). Seepage does not initiate meandering in the Drentsche Aa, but it may enhance the process of oblique aggradation by lowering the resistance to erosion of the valley side.…”
Section: Stream Evolution As a Function Of Valley Shapementioning
confidence: 99%
“…Seepage velocity is given by Darcy's Law: vs=Ksatniwhere v s is the seepage velocity, K sat is the saturated hydraulic conductivity of the soil, i is the hydraulic gradient, and n is the porosity of the soil. Seepage forces are proportional to the hydraulic gradient ( i ): τs=ρgdiwhere τ s is the seepage stress, ρ is the density of the fluid, g is gravity, and d is the grain or aggregate diameter (Fox and Wilson, ; Fox et al ., ; Midgley et al ., ). Iverson and Major () noted that a seepage force vector is responsible for destabilizing hillslopes subjected to subsurface flow and claimed seepage forces played a bigger role on slope destabilization than excess soil–water pressures.…”
Section: Introductionmentioning
confidence: 99%